PELAKSANAAN PENGEMBALIAN PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN SETELAH ADANYA PERATURAN DAERAH KABUPATEN SLEMAN NOMOR 14 TAHUN 2010 TENTANG BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN - , fajri albastra; , Dwi Haryati, S.H., M.H., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the implementation of restitution process of acquisition fees on Land and Buildings (BPHTB) in Sleman since the applicable regulation Sleman District No. 14 of 2010 regarding acquisition fees Land and Buildings and Sleman Regent Regulation No. 28 of 2011 regardingThe return of Overpaid Tax And RetributionDistrict Area.